OPTIMASI FORMULA DAN EVALUASI MASSA CETAK TABLET HISAP BERBAHAN YOGURT DENGAN METODE SIMPLEX LATTICE DESIGN - Pujianti, Ayu; Nawangsari, Desy; Febrina, Dina (Jurnal Buana Farma, 2025)
Yocanserah® yogurt contains peanuts, ginger, and lemongrass, which have potential anti-diabetic properties. Yocanserah has a limited shelf life and sour taste, so it needs to be developed into a more acceptable lozenge formulation with a longer shelf life. The purpose of this study is to optimize the formulation of yogurt-based lozenge tablets using the simplex lattice design method. The materials or factors used in the optimization were Avicel PH 102, isomalt, and SSG, with the response being flow rate and compressibility. The data were analyzed using Design Expert software with the simplex lattice design method. The yogurt-based lozenge tablet mass was made using the wet granulation method with gelatin solution as a binder. The results showed that the tablet mass with variations in Avicel PH 102, isomalt, and SSG made using the wet granulation method produced flow rate and compressibility in accordance with the specifications. The use of variations in these three ingredients had a significant effect on the flow rate and compressibility of the tablet mass with a p-value < 0.05. The optimal formula for yogurt-based lozenge molding mass was obtained with a proportion of 49% Avicel PH 102, 1% isomalt, and 5% SSG, which produced a flow rate of 5.58 g/s and compressibility of 6.69% with a resulting desirability value of 0.311.